Differences in negativity bias underlie variations in political ideology. Issue 3 (27th June 2014) - Hibbing, John R.; Smith, Kevin B.; Alford, John R.
Abstract: Disputes between those holding differing political views are ubiquitous and deep-seated, and they often follow common, recognizable lines. The supporters of tradition and stability, sometimes referred to as conservatives, do battle with the supporters of innovation and reform, sometimes referred to as liberals. Understanding the correlates of those distinct political orientations is probably a prerequisite for managing political disputes, which are a source of social conflict that can lead to frustration and even bloodshed. A rapidly growing body of empirical evidence documents a multitude of ways in which liberals and conservatives differ from each other in purviews of life with little direct connection to politics, from tastes in art to desire for closure and from disgust sensitivity to the tendency to pursue new information, but the central theme of the differences is a matter of debate. In this article, we argue that one organizing element of the many differences between liberals and conservatives is the nature of their physiological and psychological responses to features of the environment that are negative. Compared with liberals, conservatives tend to register greater physiological responses to such stimuli and also to devote more psychological resources to them. Operating from this point of departure, we suggest approaches for refining understanding of the broad relationship between political views and response to the negative. We conclude with a discussion of normative implications, stressing that identifying differences across ideological groups is not tantamount to declaring one ideology superior to another.